Ethical and socio-cultural perspectives on free-roaming cat care: The role of the Universitas Indonesia Peduli Hewan (UIPH) community in urban environmental management - Aryanti, Dela Almira; Wijaya, Sandra Turmudi (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The concept of sustainability can be applied to the management of free-roaming cat populations by humans in their environment. An increasing and uncontrolled free-roaming cat population can create problems for humans, the environment and the cats themselves. One of the efforts to manage the local cat population is carried out by the Universitas Indonesia Cares About Animals/Universitas Indonesia Peduli Hewan (UIPH) community in an urban campus environment. Such management is not necessarily in line with the concept of sustainability because it can be influenced by local community and environmental factors about which there is not much knowledge yet. Methods: Therefore, research is needed to find out more about the condition of free-roaming cats, the motivation and the role of UIPH in the UI Depok campus. A qualitative approach with in-depth interviews, direct observation and literature study is used. Findings: The results show that UIPH is a community of members from lecturers, staff and students who have concern for the survival of cats. UIPH activities include Feeding, Rescue, Fostering, Adoption and Education which are also assisted by volunteers, donations and co-sponsor collaborations. Activities by UIPH contribute to the condition of free-roaming cats that can roam freely on campus with relatively fat and healthy bodies. Conclusion: In its process, UIPH also faces problems and challenges related to the natural, social or man-made environment. But so far, they have been able to face them and carry out their routine activities. Membership, connections and ongoing programs have become an opportunity to develop community activities and regenerate wild animal awareness on campus. Novelty/Originality of this article: This study highlights the unique role of the UIPH community in managing free-roaming cat populations on an urban campus, contributing to the health and well-being of the animals. It also emphasizes the influence of local environmental and social factors in shaping sustainable wildlife management strategies.